Content Analysis of Oral Health Information in Science Textbooks: A Cross-sectional Study in Schools of Bareilly City, India - Shivangi Sharma; Jean N Murry; Sathyajith Naik N; Pallavi Vashishth; Smriti Saxena; Mongshithung N Murry (Journal of South Asian Association of Pediatric Dentistry)
Background: Oral health affects general health, way of life, and well-being. Early tooth loss is an indication that the general population is ignorant about dental disorders. Books can influence children’s thinking regarding habits and how to incorporate them into their lifestyles in addition to serving as their primary source of knowledge. This study evaluated the oral health information presented in science textbooks for standard I–X across various school boards in Bareilly city. Materials and methods: A total of 26 schools from standards I to X across a variety of boards were involved in the current survey. To conduct content analysis for different standards based on content, extent, and evidence, an assessment instrument of important components associated with oral health was employed. The data were analyzed descriptively using Microsoft Excel 2013. Results: A maximum of 17 core components were found in the ICSE Board, followed by 11 core components in the CBSE Board, and only one core component was found in the State Board of Bareilly city. About 109 messages and 74 pictures were found on the CBSE Board, and 102 messages and 55 pictures were found on the ICSE Board. Only three messages and four pictures were found on State (UP) Board. Conclusion: The textbooks from various publications used in Bareilly city State Board schools severely lack information on dental health. Included oral health-related material is essential for decreasing the prevalence of dental illnesses among teachers and students.